2006
DOI: 10.1111/j.1740-8261.2006.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Ultrasonographic Appearance of Osteochondrosis Lesions in the Canine Shoulder With Radiography, Arthrography, and Arthroscopy

Abstract: Osteochondrosis lesions in 29 shoulder joints (from 20 dogs) were evaluated with ultrasound (US) and the results were compared with survey radiography, arthrography, and arthroscopy. US was performed with a 7-12 MHz linear matrix transducer which was placed in cranio-caudal direction just distally to the acromion while the joint was adducted and maximally endorotated to visualize the caudal aspect of the humeral head. With US, the subchondral defect was completely visible in 21 joints and partially visible in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…A site was considered positive for a lesion when fragmentation and/or a subchondral bone defect were present. The severity of the lesion was graded using a four-point system, based on criteria previously reported in dogs, 15 and horses, 9 where 0 = no lesion, 1 = cartilage irregularity with a visible superficial echogenic articular surface that shows concave deviation but is contiguous, 2 = a hyperechoic subchondral bone surface with moderate irregularity and discontinuity, and 3 = complete disruption of the echogenic articular surface and a hyperechoic subchondral bone with severe irregularity and discontinuity overlaid by heterogeneously echoic material. Only the results of the experienced operator were used for analyses of ultrasonographic sensitivity and specificity, and the ability of ultrasonography to predict severity of the lesions.…”
Section: Methodsmentioning
confidence: 99%
“…A site was considered positive for a lesion when fragmentation and/or a subchondral bone defect were present. The severity of the lesion was graded using a four-point system, based on criteria previously reported in dogs, 15 and horses, 9 where 0 = no lesion, 1 = cartilage irregularity with a visible superficial echogenic articular surface that shows concave deviation but is contiguous, 2 = a hyperechoic subchondral bone surface with moderate irregularity and discontinuity, and 3 = complete disruption of the echogenic articular surface and a hyperechoic subchondral bone with severe irregularity and discontinuity overlaid by heterogeneously echoic material. Only the results of the experienced operator were used for analyses of ultrasonographic sensitivity and specificity, and the ability of ultrasonography to predict severity of the lesions.…”
Section: Methodsmentioning
confidence: 99%
“…Images were again reviewed and lesions scored retrospectively using a 4-point system, based on lesion description in a study of the dog (Vandevelde et al 2006), where 0 = no lesion, 1 = cartilage irregularity with a visible superficial echogenic articular surface that shows concave deviation but is continuous, 2 = a hyperechoic subchondral bone surface with moderate irregularity and discontinuity, and 3 = complete disruption of the echogenic articular surface and a hyperechoic subchondral bone surface with severe irregularity and stair like discontinuity overlaid by heterogeneously echoic material (Fig 4). Disruption of subchondral bone was deemed to be a fragment.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Lesions are flattened or irregular areas of the subchondral bone, especially in the proximal aspect of the trochlear ridges (TR), and may be accompanied by loose fragment(s). However, no abnormality can be seen on radiographs if the subchondral bone is unaffected (McIlwraith 1996;Vandevelde et al 2006). In one study, OCD lesions were undetected in 40% of 72 FP joints; however, they were found during arthroscopy and more than half were worse than expected (Sullins 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…65,66 The caudal humeral head is imaged with the transducer in a craniocaudal orientation, and the shoulder is rotated medially to expose the articular cartilage. Articular cartilage defects of the caudal aspect of the humeral head (and femoral condyle) may be detected ultrasonographically, depending on the size and position of the defect.…”
Section: Abnormal Findingsmentioning
confidence: 99%